1991
DOI: 10.1200/jco.1991.9.1.85
|View full text |Cite
|
Sign up to set email alerts
|

4-Hydroperoxycyclophosphamide purging of breast cancer from the mononuclear cell fraction of bone marrow in patients receiving high-dose chemotherapy and autologous marrow support: a phase I trial.

Abstract: We designed an ex vivo bone marrow treatment for breast cancer patients receiving high-dose chemotherapy and autologous bone marrow support (ABMS), using 4-hydroperoxycyclophosphamide (4-HC), an active derivative of cyclophosphamide with known activity against breast cancer. This phase I bone marrow purging trial used ficoll-separated mononuclear cells (MNC) (devoid of granulocytes and RBCs), as opposed to the buffy coat. Twenty-five patients with metastatic breast cancer were studied. Patients received three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

1991
1991
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(33 citation statements)
references
References 0 publications
0
32
0
1
Order By: Relevance
“…In a subsequent clinical phase 1 trial, a significant delay in leukocyte recovery could be correlated with the mafosfamide concentration used for tumour cell purging. 24 The combination of mafosfamide incubation with immunotoxin treatment was examined by O'Briant et al 25 in an in vitro study. They described 2.2-5.4 log tumour cell reduction from a 1:10 breast cancer cell dilution in irradiated marrow cells.…”
Section: Discussionmentioning
confidence: 99%
“…In a subsequent clinical phase 1 trial, a significant delay in leukocyte recovery could be correlated with the mafosfamide concentration used for tumour cell purging. 24 The combination of mafosfamide incubation with immunotoxin treatment was examined by O'Briant et al 25 in an in vitro study. They described 2.2-5.4 log tumour cell reduction from a 1:10 breast cancer cell dilution in irradiated marrow cells.…”
Section: Discussionmentioning
confidence: 99%
“…3,4,[32][33][34] However, there have been no prospective randomized trials to determine if these techniques diminish the probability of relapse or progression after HDC and BM or PBSC infusion. Randomized clinical trials designed to evaluate an effect of purging on relapse or progression will be difficult, if not impossible, to perform because available HDC regimens do not eradicate endogenous disease in the majority of patients with stage IV breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16] In more recent preclinical studies the combination of imatinib and mafosfamide has been shown to exert impressive synergistic antitumor activity against CML cells. 17 This stimulated our interest in using this drug combination in an ex vivo autograft-purging regimen.…”
Section: Introductionmentioning
confidence: 99%